Acute toxicity evaluation and antidyslipidemic potential of Retama sphaerocarpa aerial parts in Triton WR-1339 induced hyperlipidemic rats - Adil Qabouche; Ismail Bouadid; Ayoub Amssayefa; Ahmed El-Haidani; Mohamed Eddouks (Creative Pharma Assent, 2026)
Background: Dyslipidemia constitutes a major risk factor for cardiovascular diseases. Although conventional lipid-lowering therapies are effective, their prolonged use is associated with adverse effects, highlighting the need for safer natural alternatives. Species of the genus Retama, including Retama sphaerocarpa, have been reported to possess various pharmacological properties, including antioxidant, hepatoprotective, anti-inflammatory, and hypoglycemic activities. However, no study to date has evaluated the antidyslipidemic potential of R. sphaerocarpa. This study was conducted to evaluate both the acute oral toxicity and the antidyslipidemic effect of the Retama sphaerocarpa aqueous extract (RSAE) in a Triton WR-1339-induced hyperlipidemic rat model. Methodology: The acute toxicity study of RSAE was conducted in accordance with OECD Guideline 423. RSAE was administered orally as a single dose of 2000 mg/kg, and the rats were monitored for any signs of toxicity or mortality. Hematological and biochemical parameters were assessed 24h post-administration of RSAE. The antidyslipidemic effect of RSAE (400 mg/kg) was studied in Triton WR-1339-induced dyslipidemia in Wistar albino rats. Results and discussion: Results showed no mortality or clinical signs of toxicity following RSAE administration; hematological and biochemical parameters remained unaltered after 24 hours post-treatment. The RSAE demonstrated antioxidant activity (IC₅₀ = 241.45 μg/mL). For the lipid-lowering assessment, RSAE pretreatment significantly reduced plasma TC levels by 51.1% (p<0.01), TGs by 60.2% (p<0.01), and LDL-c by 73.5% (p<0.01), while increasing HDL-c levels (p<0.01). Conclusion: Results from the present study highlight the potential of Retama sphaerocarpa in the prevention and management of dyslipidemia.